Supplementary Data Report for 'Eddy Heat Flux Across the Antarctic Circumpolar Current Estimated from Sea Surface Height Standard Deviation' - Foppert, Annie (DigitalCommons@URI, 2017)
These are supporting codes and files for the manuscript 'Eddy heat flux across the Antarctic Circumpolar Current estimated from sea surface height standard deviation' written by A. Foppert, K. A. Donohue, D. R. Watts and K. L. Tracey, and accepted for publication in the Journal of Geophysical Research Oceans. The following document explains the codes used for analysis of the data used in the manuscript and files used to create the figures.